2010
DOI: 10.1667/rr1769.1
|View full text |Cite
|
Sign up to set email alerts
|

Association between Normal Tissue Complications after Radiotherapy and Polymorphic Variations inTGFB1andXRCC1Genes

Abstract: Genetic predictive biomarkers of radiosensitivity are being sought to individualize radiation treatment of cancer patients. In this pilot case-control study, we tested the association between TGFB1 T869C codon 10 Leu/Pro (rs1982073), XRCC1 G28152A codon 399 Arg/Gln (rs25487), and XRCC3 C18067T codon 241 Thr/Met (rs861539) single-nucleotide polymorphisms (SNPs) and late reaction to radiotherapy in 60 nasopharyngeal cancer patients. Subcutaneous and deep tissue fibrosis was scored using the RTOG/EORTC grading sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
49
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 30 publications
3
49
2
2
Order By: Relevance
“…Our results were in line with findings reported by other studies with relatively large sample sizes (16,17). However, our results were in contrast to those reported by 3 studies performed in Saudi Arabian NPC patients by Alsbeih et al (4,5,18). Our results indicated a trend of possible association between rs861539 of XRCC3 and radiation-induced fibrosis in Chinese NPC patients, but not rs25487 of XRCC1.…”
Section: Most Significant Omnibus Test ------------------------------supporting
confidence: 90%
See 1 more Smart Citation
“…Our results were in line with findings reported by other studies with relatively large sample sizes (16,17). However, our results were in contrast to those reported by 3 studies performed in Saudi Arabian NPC patients by Alsbeih et al (4,5,18). Our results indicated a trend of possible association between rs861539 of XRCC3 and radiation-induced fibrosis in Chinese NPC patients, but not rs25487 of XRCC1.…”
Section: Most Significant Omnibus Test ------------------------------supporting
confidence: 90%
“…Since different patients may present with different degrees of skin fibrosis despite receiving identical treatment, it was hypothesized that the severity of such complications may be genetically determined. Previous studies investigated the association of single-nucleotide polymorphisms (SNPs) in genes involved in DNA repair, such as X-ray repair cross-complementing protein 1 (XRCC1) rs25487 (c.1196A>G, p.Gln399Arg) and X-ray repair cross-complementing protein 3 (XRCC3) rs861539 (c.722C>T, p.Thr241Met) with late complications in various types of cancer (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, cancer researchers have investigated the link between SNPs and various endpoints such as drug resistance in chemotherapy, radiosensitivity in radiation therapy, and cancer susceptibility (Alsbeih et al, 2010). A number of studies have suggested that SNPs might contribute along with other factors to the development of various human malignancies (Zhou et al, 2007;Chiu et al, 2008).…”
mentioning
confidence: 99%
“…Some of these studies establish predictive models based on multiple SNPs. Examples are given in references [5][6][7][8][9][10][11][12]. For several reasons, such approach seems attractive.…”
mentioning
confidence: 99%
“…We have taken a closer look at four different studies that established predictive models based on multiple SNPs [5][6][7][8]. All studies were relatively small with sample sizes between 37 and 69 patients.…”
mentioning
confidence: 99%